2019
DOI: 10.1155/2019/4168472
|View full text |Cite
|
Sign up to set email alerts
|

Memantine Differentially Regulates Tau Phosphorylation Induced by Chronic Restraint Stress of Varying Duration in Mice

Abstract: Exposure to chronic psychiatric stress has been linked to Alzheimer’s disease-related tau hyperphosphorylation and abnormalities in glutamate neurotransmission. However, the pathological relationship between glutamatergic dysfunction and tau phosphorylation in the cerebral cortex under chronic psychiatric stress is not fully understood. The present study investigated the effects of memantine (MEM, 5 and 10 mg/kg), an uncompetitive N-methyl-D-aspartate (NMDA) receptor antagonist, on chronic restraint stress- (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 85 publications
1
9
0
Order By: Relevance
“…Similar to previous studies, the present study confirmed the anxiogenic, and the depressing effects induced by CIS (Ampuero et al, 2015; Chen, Li, Zhao, & Yang, 2008; Liu et al, 2019). In the OFT, a decrease in the time spent in the central zone is considered to reflect the fear of entering and exploring a novel environment and is associated with increased anxiety levels of the animal.…”
Section: Discussionsupporting
confidence: 92%
“…Similar to previous studies, the present study confirmed the anxiogenic, and the depressing effects induced by CIS (Ampuero et al, 2015; Chen, Li, Zhao, & Yang, 2008; Liu et al, 2019). In the OFT, a decrease in the time spent in the central zone is considered to reflect the fear of entering and exploring a novel environment and is associated with increased anxiety levels of the animal.…”
Section: Discussionsupporting
confidence: 92%
“…Accordingly, significant diminution of p-Tau [Ser396] was found after RL-208 administration. To our knowledge, memantine is also described as able to reduce tau phosphorylation [65][66][67], linking the RL-208 antagonist action on NMDAR again with the neuroprotectant effectivity in SAMP8.…”
Section: Discussionmentioning
confidence: 86%
“…Previous data showed that acute stress or corticosterone administration may cause hypofunction of NMDA receptors by inhibiting D-serine release, despite of increasing glutamate (Wang et al, 2021). Long-term hypofunction of NMDA receptor, on the condition of chronic stress, might cause compensatory NMDA receptor expression, as showed in published data (Liu et al, 2019;Lorigooini et al, 2020) Sketch map for the mechanisms of isorhynchophylline on CUMS induced emotional disorders and cognitive impairment.…”
Section: Discussionmentioning
confidence: 92%
“…Synaptic structure is the biological basis of learning and memory ( Luscher and Malenka, 2012 ), normal synaptic transmission requires presynaptic glutamate and D-serine to bind to NMDA receptors to maintain synaptic plasticity and cognitive function ( Hardingham and Bading, 2010 ). It’s reported that chronic stress induced glutamate elevation ( Garcia-Garcia et al, 2009 ; Hill et al, 2012 ; Willner, 2017 ) and NMDA receptors expression increasing ( Liu et al, 2019 ; Lorigooini et al, 2020 ) in hippocampal tissue, indicating hyperfunction of NMDA receptors. On the other hand, chronic stress induced D-serine deficit ( Wang et al, 2017 ), indicating hypofunction of NMDA receptors.…”
Section: Discussionmentioning
confidence: 99%